Big Brain Imaging: A Quest to Map the Most Complex Organ - The Human Brain - Zhang, Tony (The Meducator, 2014)
In the past several decades, brain-mapping has emerged as a revolutionary process to further understand the relationship between neural structure and function.1 With increased computing power, computer-mapping in threedimensional standard brain atlases can now be produced at nearly cellular resolution. The recent commencement of one of the world’s largest scientific projects to date, the Human Brain Project (HBP), aims to synthesize massive data generated by research institutions across Europe. Forschungszentrum Jülich (Research Centre Juelich), a member of the HBP, currently has the highest resolution 3D brain atlas in the world, the BigBrain, at 20-micrometer resolution.2 The author outlines the significance of observer-independent mapping and the different visual and objective techniques used to map the primary motor cortex.